ATTITUDES AND KNOWLEDGE OF STATE JUNIOR GIRLS IN BANJAR DISTRICT REGARDING BLOOD ADDING TABLETS - Fatimatuzzahra, Siti Nor Amanda; 'Aien, Noor; Kiftiah, Mariatul; Heriawan, Ahmad; Rafieannor, Rafieannor; Rahmadi, Rahmadi; Normawarni, Halisa; Anggara, Norma (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
Iron deficiency anemia is a problem that is often found and attacks all age groups. Anemia can attack anyone, but most often attacks women of childbearing age, especially teenage girls. Adolescent girls are still a public health problem. The teenage girl period should be an important phase in preparation for becoming a mother-to-be so that she is required to fulfill nutritional needs. The effects of anemia are slowed growth and development, fatigue, decreased endurance and increased susceptibility to poisoning. Adolescent girls have a higher risk of experiencing anemia than adolescent boys. Iron lost due to menstruation and iron needs that are not yet met from food can be met by consuming blood supplement tablets. The aim of this research was to determine the level of female students' knowledge and the importance of taking blood supplement tablets as teenagers. The subjects in this research were 125 female students in class 8 A-H of SMP Negeri 3 Martapura, Banjar Regency. To obtain the sample in this study using the Slovin formula with an allowance of 5%, 95 female students were obtained in this research sample which shows that the average of 95 female students with 20 questions obtained a score of 15.03, median 15/20, range 9 /20 in the very good category.